1967
DOI: 10.1210/endo-81-6-1278
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 17α-Methylandrostenediol and 17α-Methyltestosterone by the Rat Adrenal Glandin Vitro

Abstract: Rat adrenal tissue in vitro oxidized 17o;-methylandrost-5-ene-3j3, 17/3-diol (MAD) to 17a-methylandrost-4-en-17j3-ol-3-one (17«-methyltestosterone). Both MAD and 17o-methyltestosterone were further metabolized to at least 5 ultraviolet light-absorbing products. Evidence was obtained for the identification of the major product as ll/3-hydroxy-17a-methyltestosterone. The next most abundant product was probably ll-oxo-17a-methyltestosterone. The other products were formed in lesser amounts and little progress was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…adrenal homogenates did not inhibit the conversion of progesterone to corticosterone (2). In addition, it has been shown that rat adrenal tissue oxidizes MAD to MT (5). These latter observations are consistent with the concept that treatment of rats with MAD leads to inhibition of corticosterone formation by a mechanism involving conversion of the MAD to MT and the competitive inhibition of 11/3-hydroxylation of DOC by the MT.…”
supporting
confidence: 84%
“…adrenal homogenates did not inhibit the conversion of progesterone to corticosterone (2). In addition, it has been shown that rat adrenal tissue oxidizes MAD to MT (5). These latter observations are consistent with the concept that treatment of rats with MAD leads to inhibition of corticosterone formation by a mechanism involving conversion of the MAD to MT and the competitive inhibition of 11/3-hydroxylation of DOC by the MT.…”
supporting
confidence: 84%
“…In addition, Brownie and Skelton* found that steroid 11/8-hydroxylase activity was low in adrenal homogenates and mitochondria from MAD-treated rats, leading to an accumulation of 11-deoxycorticosterone (DOC). MAD is converted to 17a-methyltestosterone (MT; 17a-methyl-4-androstene-17/3-ol-3-one) in the adrenal 4 and MT is similar to testosterone' in being an inhibitor of the 11/3-hydroxylation of DOC." This has led to general agreement that increased secretidn of the hypertensinogenic steroid DOC 7 is involved in the pathogenesis of MADinduced hypertension.…”
Section: S Keltonmentioning
confidence: 99%